Are former professional athletes and native better coaches? Evidence from Spanish basketball - del Corral, J.; Maroto, A.; Gallardo, A. (Journal of Sports Economics, 2017)
This article analyzes the efficiency of coaches in the Top Spanish Basketball League and what determines this efficiency. To accomplish this, a stochastic production function is estimated. Among others, the inefficiency determinants considered are whether the coach is an ex-professional player and whether he is from Spain. The results demonstrate that foreign coaches are more efficient. To build upon these results, a new approach to estimate the efficiency of coaches, in which efficiency is obtained by comparing their performance with expectations attained from betting odds, is proposed. The results were principally reinforced.